Existence and stability of periodic solutions for a forced pendulum with time-dependent damping - Fang-Fang Liao (Boundary Value Problems, 2018)
Abstract In this paper, we study the existence, multiplicity and stability of periodic solutions for a forced pendulum with time-dependent damping. The proof is based on the third order approximation method and a suitable version of the Poincaré–Birkhoff fixed point theorem.